Higher fiber‐tract myelin levels predict lower longitudinal rates of fibrillar tau independent of amyloid. (20th December 2022) - Rubinski, Anna; Franzmeier, Nicolai; Dewenter, Anna; Luan, Ying; Smith, Ruben; Strandberg, Olof; Ossenkoppele, Rik; Dichgans, Martin; Hansson, Oskar; Ewers, Michael; ,
Abstract: Background: Fibrillar tau progresses from initial epicenters of high tau accumulation to closely connected cortical regions during the course of Alzheimer's disease (AD). Myelin ensheaths the interregional axonal connections, where ontogenetically late and thinly myelinated fibers are more susceptible to damage and may propel the propagation of fibrillar tau, as suggested by post‐mortem data (https://doi.org/10.1093/brain/awv236). Here we tested for the first time, in two independent samples of AD patients whether 1) regions connected to epicenters by more thickly myelinated fiber tracts show lower rates of tau‐PET accumulation, and 2) differences in regional amyloid‐PET levels explain the association between myelin and tau‐PET accumulation. Methods: We included two independently recruited samples with longitudinal AV1451‐tau‐PET of amyloid‐PET positive non‐demented and demented individuals (ADNI: n = 123, mean FU = 1.53[0.69‐3.95] years; BioFINDER: n = 39, mean FU = 1.87[1.21‐2.78] years). Adopting our previously established connectivity‐based prediction approach (https://doi.org/10.1126/sciadv.abd1327 ), we first determined tau epicenters by selecting the top 10% ROIs with highest tau‐PET uptake. Next, we computed for each tau epicenter the connectivity‐based distance to the ROIs in the remainder of the brain, based on resting‐state fMRI data from the Human Connectome Project (HCP). To determine the myelin levels in the underlying fiber tracts, we reconstructed fiber‐tracts for each epicenter‐to‐ROI pair based on DWI data from HCP and extracted regional myelin‐water‐fraction (MWF) values for each tract from an overlaid myelin‐water‐imaging atlas (https://doi.org/10.1111/jon.12657 ). In order to test whether fiber tract myelination attenuates the connectivity‐based tau‐spreading, we tested the interaction between epicenter connectivity‐based distance and MWF in the corresponding fiber‐tracts on the rate of tau‐PET accumulation in the connected regions. In a sensitivity analysis restricted to the sufficiently powered ADNI‐sample, we controlled the interaction analysis for regional amyloid‐PET levels within target ROIs. Results: We found a significant interaction of connectivity‐based distance by fiber‐tract MWF on the rate of tau‐PET accumulation (ADNI: β = 2.08, p = 0.009; BioFINDER: β = 1.876, p = 0.028; Figure 1), such that regions connected by highly myelinated fiber‐tracts showed lower rates of connectivity‐dependent tau accumulation. When controlling for regional amyloid‐PET levels, the interaction remained significant (ADNI: β = 2.23, p = 0.006). Conclusion: Higher fiber‐tract myelination is associated with lower rates of tau progression in AD, independent of beta‐amyloid.